A PET-CT study on neuroinflammation in Huntington's disease patients participating in a randomized trial with laquinimod. Issue 2 (3rd April 2023) - Roussakis, Andreas-Antonios; Gennaro, Marta; Gordon, Mark Forrest; Reilmann, Ralf; Borowsky, Beth; Rynkowski, Gail; Lao-Kaim, Nicholas P; Papoutsou, Zoe; Savola, Juha-Matti; Hayden, Michael R; Owen, David R; Kalk, Nicola; et al.
Abstract: Microglia activation, an indicator of central nervous system inflammation, is believed to contribute to the pathology of Huntington's disease. Laquinimod is capable of regulating microglia. By targeting the translocator protein, 11 C-PBR28 PET-CT imaging can be used to assess the state of regional gliosis in vivo and explore the effects of laquinimod treatment. This study relates to the LEGATO-HD, multi-centre, double-blinded, Phase 2 clinical trial with laquinimod (US National Registration: NCT02215616). Fifteen patients of the UK LEGATO-HD cohort (mean age: 45.2 ± 7.4 years; disease duration: 5.6 ± 3.0 years) were treated with laquinimod (0.5 mg, N = 4; 1.0 mg, N = 6) or placebo ( N = 5) daily. All participants had one 11 C-PBR28 PET-CT and one brain MRI scan before laquinimod (or placebo) and at the end of treatment (12 months apart). PET imaging data were quantified to produce 11 C-PBR28 distribution volume ratios. These ratios were calculated for the caudate and putamen using the reference Logan plot with the corpus callosum as the reference region. Partial volume effect corrections (Müller–Gartner algorithm) were applied. Differences were sought in Unified Huntington's Disease Rating Scale scores and regional distribution volume ratios between baseline and follow-up and between the two treatment groups (laquinimod versus placebo). No significant change in 11 C-PBR28 distribution volume ratios was found post treatment in the caudate and putamen for both those treated with laquinimod ( N = 10) and those treated with placebo ( N = 5). Over time, the patients treated with laquinimod did not show a significant clinical improvement. Data from the 11 C-PBR28 PET-CT study indicate that laquinimod may not have affected regional translocator protein expression and clinical performance over the studied period. Abstract : This is a longitudinal study in Huntington's disease with laquinimod (microglia modulator) and 11 C-PBR28 PET (specific marker of reactive gliosis). Roussakis and Gennaro report that 12-month long laquinimod treatment (0.5 or 1 mg daily versus placebo) does not affect regional microglia activation. Graphical Abstract: Graphical Abstract